The Influence of Satisfaction toward Loyalty of Adolescent Consumers Mujigae Resto in Bogor City - Fidaa Nafiisah; Moh Djemdjem Djamaludin (Department of Family and Consumer Sciences, Faculty of Social and Human Ecology, IPB University, 2020)
As the globally popularity of South Korean culture called Korean wave is hitting around the world, Korean food has been drawing people’s attention and Korean restaurants have been developing in recent years. One of them is offered by a restaurant franchise called Mujigae Resto which can be found in many areas of Indonesia including Bogor City. This study aims to analyze the influence of satisfaction toward loyalty of consumers of Mujigae Resto in Bogor City. This study was a cross-sectional study design which used an online survey method. As many as 150 adolescents have participated in this survey. The sample criteria were individuals aged 16-18 years, residing in Bogor City, and had bought foods in Mujigae Resto at least two times in the last six months. The analysis included a descriptive analysis, Spearman correlation test, and hypothesis test with the Structural Equation Modeling (SEM) using the Analysis of Moment Structures (AMOS) program. The results showed that consumer adolescents in this study, generally, had a satisfaction in a moderate level and loyalty in a low level. Consumer satisfaction significantly affected consumer loyalty on Mujigae Resto.